Application of CRRC 1 000 A/3 300 V IGBT in Urban Rail Traction System - Yanping CHEN; Yan CHEN; Mingyi CHEN; Chaoqun WAN (机车电传动)
The background of the application of the CRRC TIM1000NSM33 IGBT on the traction system of Wuxi metro line 2 was expounded. The feasibility and reliability of the device substitution were compared and analyzed from the aspects of IGBT technology route and traction system selection design. The results show that, for having adopted the upgraded technology route, the performance, index and reliability of the independent IGBT are higher than the original imported brands and meet the substitution requirements. In addition, the application problems of domestic IGBT devices in vehicle loading assessment were analyzed in detail, and effective measures were put forward to make the domestic IGBT successfully applied to Wuxi metro, and extended to other projects and fields.